The association between school policies, practices, and public perception of trans youth in the U.S. Issue 1 (2nd January 2020) - Persinger, Lisa L.; Persinger, Joey D.; Abercrombie, Sara
Abstract: In this time, when social climate is particularly divisive with decreasing support for trans people in the U.S., we explore the general population's attitudes regarding protections for trans children. A survey of a nationally-representative sample of 765 U.S. adults yielded perspectives regarding policies and practices impacting trans children in schools. Analyses on the predictive value of social group membership characteristics (e.g., political ideology, religion), implicit and explicit attitudes, experiences, knowledge of terminology related to trans children, as well as other demographics predict support for safe and inclusive school policies and practices as well as explicitly exclusive policies and practices impacting trans students in schools. A new implicit association test and semantic differential scale were created for this study. Three sets of analyses addressed research goals. Adults expressing favorable explicit attitudes toward trans students are the strongest supporters of policies and practices that inclusively protect them. Some of our analyses show knowing someone trans is not always influential in decisions to support inclusive policies and practices for trans students. On exclusionary policies and practices, parents were more supportive of excluding protections than non-parents. Religious affiliations and support mirror prior research.